Assessing the propagation of uncertainties in multi-objective optimization for agro-ecosystem adaptation to climate change. (April 2015) - Holzkämper, A.; Klein, T.; Seppelt, R.; Fuhrer, J.
Abstract: It is widely acknowledged that uncertainty needs to be accounted for in climate impact studies, be it in scenario analyses or optimization applications. In this study we investigate how climate and crop model uncertainties affect multi-objective optimization outputs aiming to identify optimum agricultural management adaptations for Western Switzerland. Results are visualized by ternary plots that map optimum management measures, crop yield, erosion and leaching with associated uncertainties for navigating through the optimum adaptation space. We find that the relevance of climate model vs. parameter uncertainty can differ substantially depending on the prioritization of objectives and local conditions. The optimum choice of irrigation level was found to be the decision variable subject to greatest uncertainty particularly on coarser soil. This finding suggests that for the long-term planning of irrigation infrastructure and management, a robust adaptation approach is required for approaching unavoidable uncertainty from a risk management perspective. Highlights: Multi-objective solutions are found to be fairly robust for most objective weights. Effects of climate and parameter uncertainties depend on objective weights and location. Future irrigation management is subject to greatest uncertainties in the case study. Ternary plots visualize the optimum adaptation space and highlight robust solutions.